1987
DOI: 10.1038/327482a0
|View full text |Cite
|
Sign up to set email alerts
|

Myristylation of picornavirus capsid protein VP4 and its structural significance

Abstract: We have obtained evidence that poliovirus and other picornavirus particles are specifically modified by having myristic acid covalently bound to a capsid protein. The electron density map of poliovirus confirms the position of the myristate molecule and defines its location in the virus particle. Analogies with other myristylated proteins suggest that the myristate moiety in picornaviruses may be involved in capsid assembly or in the entry of virus into cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
292
1
6

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(303 citation statements)
references
References 0 publications
4
292
1
6
Order By: Relevance
“…In the case of the transforming protein of Rous sarcoma virus (pp60""c), the myristyl group is clearly necessary, although perhaps not sufficient, to convey membrane-associating properties (Kaplan et al, 1990). In the case of the poliovirus capsid protein, VP4, the myristyl group appears to provide a hydrophobic anchor between subunits on the coat surface and plays a structural role in capsid assembly (Chow et al, 1987). The structure of the mammalian C-subunit provides the first example of how a myristyl group can contribute to the stability of a soluble protein.…”
Section: Myristylationmentioning
confidence: 99%
“…In the case of the transforming protein of Rous sarcoma virus (pp60""c), the myristyl group is clearly necessary, although perhaps not sufficient, to convey membrane-associating properties (Kaplan et al, 1990). In the case of the poliovirus capsid protein, VP4, the myristyl group appears to provide a hydrophobic anchor between subunits on the coat surface and plays a structural role in capsid assembly (Chow et al, 1987). The structure of the mammalian C-subunit provides the first example of how a myristyl group can contribute to the stability of a soluble protein.…”
Section: Myristylationmentioning
confidence: 99%
“…However, not all myristylated proteins are membrane bound and myristylation in some cases is not sufficient for association with the lipid bilayer [32]. In addition, structural studies of the N-myristylated picornavirus capsid protein VP4 have shown that the fatty acid resides in a hydrophobic pocket formed by amino acid side chains [33]. Since alkaline extraction readily removes the 43 kDa protein from the membrane without modification of the myristylated Nterminus [28], Carr et al [29] have suggested that the fatty acid does not anchor 43 kDa protein to the membrane by imbedding in the lipid bilayer, but may instead be important in interactions between the 43 kDa protein and the AChR.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…One or two copies of VP0 remain uncleaved in each capsid, the functional significance of this observation being unclear. Picornavirus proteins are non-glycosylated but VP4 (and VP0) is modified at its N terminus by linkage to myristic acid (Chow et al, 1987). This fatty acid has been shown to be associated with viruses of several different families, and an involvement in receptor binding, uncoating or capsid assembly has been suggested (Chow et al, 1987).…”
Section: Structure Of Picornavirusesmentioning
confidence: 99%
“…Picornavirus proteins are non-glycosylated but VP4 (and VP0) is modified at its N terminus by linkage to myristic acid (Chow et al, 1987). This fatty acid has been shown to be associated with viruses of several different families, and an involvement in receptor binding, uncoating or capsid assembly has been suggested (Chow et al, 1987). In addition to this modification, the potential for VP2 and VP4 to be phosphorylated by cellular kinases, thereby destabilizing the capsid, may play a role in uncoating of the nucleic acid (Ratka et al, 1989).…”
Section: Structure Of Picornavirusesmentioning
confidence: 99%